Strike to Win: Can Polish Feminists Turn Protest Into Power? - Beaty, Thalia (Dissent (0012-3846))
The article discusses several mass opposition movement and protests organized by feminist groups in Poland. Topics discussed include the marches of radical feminists group Manifa with the slogan "Against the Violence of Power" which talk about unpaid labor of women, abortion, and rights of sex workers and disabled people, the opposition of the Committee for the Defense of Democracy or KOD on the attacks of Law and Justice on independece of judiciary in Poland, and the limited access on contraception, sex education and abortion.